Lingkungan Menyenangkan dalam Pendidikan Anak Usia Dini: Pemikiran Montessori - Hidayatulloh, M. Agung (Nadwa, 2014)
This article presents the description of a pleasant environment according to the Montessori method. fun environment characteristics and implications for the sustainability of early childhood education in Indonesia is also a discus-sion section. Montessori considers the environment as a key children spon-taneous learning. Because the child is an active agent in its environment, Montessori suggested that the environment here should be fun for children and also provide opportunities for the development of the potential of each individual. In addition there is ease of access, with full responsibility, and freedom of movement, in the early child hood environment should be designed in such a way to make it look real, natural, and beautiful.